The impact of suicide rates on admissions to emergency medical services and the role of education and employment - Boğa, Erkan (The European Research Journal, 2025)
Objectives: In this research, it was aimed to evaluate the impact of suicide rates on admissions to emergency medical services (EMS) and the role of education and employment. Methods: In the research, the Ministry of Health of the Republic of Turkey parameter of cases per EMS between 2002 and 2022, deaths due to suicide, education and employment data from the World Bank Turkey Report were used. Results: Mean cases per EMS in Türkiye for 2002-2022 time period had 1,512.30±560.82 (range: 653-2,428). Mean suicide mortality range was 2.51±0.32 (range: 2.20-3.20). Mean school enrollment rates were 95.45±2.70 ranged from 87.90 to 98.52. Mean employment rate was 44.08±2.12 (range: 41.15-47.37). Cases per EMS was significantly correlated with suicide mortality (r=-0.777; P<0.01), school enrollment (r=-0.832; P<0.01) and employment rate (r=0.704; P<0.01). Year controlled partial correlation analysis results showed that there was a significant correlation between cases per EMS and employment rate (r=0.653; P<0.01). School enrollment and employment on cases per EMS, effect of suicide mortality on cases per EMS was statistically significant (B=-2121.23; P<0.01). Effects of school enrollment and employment on cases per EMS were insignificant (P>0.05). Conclusions: EMS units are very effective in reducing suicide mortality rates at both the correlation and regression levels. This effectiveness is similar across different education and employment groups. To reduce suicide mortality, it is necessary to focus on EMS access rather than EMS effectiveness.